Pages of the History of Russian Medicine: Academician of the Russian Academy of Sciences, Doctor of Medical Sciences, Professor Alexey Petrovich Golikov – Doctor, Scientist, Citizen (to the 100th Anniversary of His Birth) - S. A. Boytsov; R. I. Stryuk; A. A. Golikova; A. G. Evdokimova (Рациональная фармакотерапия в кардиологии)
The main stages of the creative path of the scientist with a world-famous, professor, the Honored Worker of Science of the Russian Federation, Academician of the Russian Academy of Sciences Alexey Petrovich Golikov are presented in the article.